Pengaruh Harmonisa Pada Inverter di Pembangkit Tenaga Surya Terhadap Pembebanan - Fauzi, Rama; Roza, Indra (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2023)
This research was conducted to look at the characteristics of current and voltage harmonics in an electric power system loaded with non-linear loads. The inverter is a non-linear load that is widely used in industry, government agencies and households. In theory, the inverter is a non-linear load that can produce harmonics in the electric power system, where the resulting harmonics will flow to the source and to the load. Therefore, this research is to look at the characteristics of harmonics in the power system produced by a three-phase inverter, where this research was carried out in two scenarios. The first scenario is to see current and voltage harmonics under unloaded inverter conditions and the second scenario is to see current and voltage harmonics under loaded inverter conditions. Both of these scenarios are carried out with a varied source voltage. In this study using a passive filter in the form of a single-tuned filter, the simulation results were carried out on conditions before the filter was installed for a THDv value of 38.94% and after the filter was installed it was 27.43%. The difference in value, before installing the filter and after installing the filter is 11.51%. this still exceeds the 1952 IEEE 512 standard, so more than one filter is needed to reduce harmonics